Successful weaning from the invasive respiratory support after nusinersen treatment in a child with SMA type 1: A case report - Pan, Meiling; Shi, Jun; Miao, Hongjun; Zhang, Qin (Frontiers in Pediatrics, 2023)
Background: Spinal muscular atrophy (SMA) is an autosomal recessive disease, which can be classified into 4 types according to the symptom onset age and the highest physical developmental milestone. Among them, type 1 SMA is the most severe form that affects infants younger than 6 months. Permanent assisted ventilation is usually needed for infants with type 1 SMA before the age of 2 years due to the rapid progression of disease. Nusinersen can improve the motor function of SMA patients, but its effect on respiratory function varies.In the present study, we reported a case of child with type 1 SMA who was successfully weaned from the invasive respiratory support after nusinersen treatment. Case presentation: A girl aged 6 years and 5 months was admitted for SMA in the Children’s Hospital of Nanjing Medical University for 18 times. She received the first administration of nusinersen in November 2020 at the age of 5 years and 1 month.At the age of 6 years and 1 month following 6 loading doses, we tried to wean the child from the invasive ventilation for non-invasive respiratory support using a nasal mask.At present, the patient shows oxygen saturation (SpO2) above 95% without ventilator support during the daytime, and no signs of dyspnea. A non-invasive home ventilator was used at nighttime for the sake of safety. The CHOP INTEND score increased by 11 points from the first loading dose to the sixth. She can now move her limbs against gravity, take in food orally and perform partial vocal function. Conclusions: We reported a child with type 1 SMA who was successfully weaned from the 2-years invasive ventilation after 6 loading doses,and now only need non-invasive ventilation 12 h per day. It is suggested that even a late nusinersen treatment can improve respiratory and motor function in SMA patients, and wean them from mechanical ventilation, thus improve the quality of life and reduce the medical cost.